THE TOURISM DESTINATION BRAND IMAGE OF LOVINA BEACH: A FACTOR ANALYSIS - Kusyanda, Made Riki Ponga; Suriani , Ni Made; Andiani , Nyoman Dini (Universitas Pendidikan Ganesha, 2023)
This study is aimed in how the Brand Image attribute can attract the destination image of Lovina Beach. The factor analysis was used to describe the variety of factors that can contribute to reflecting the value of destination image and destination brand image. This study was analyzed based on quantitative research, by using purposive sampling with 100 respondents. The result of the study is based on the analysis results obtained 2 factors that can explain 7 factors, namely factor 1 as the most visited and recognized tourism destination brand which associates 3 variables, while factor 2 is The Lovina Brand name as a Unique Selling Point which associates 3 variables, where these two factors when added together are able to explain 74% of the variation in factor